LEGAL CONSEQUENCES OF THE SUPREME COURT'S DECISION IN THE CASE OF A REQUEST FOR POSTPONEMENT OF DEBT PAYMENT OBLIGATIONS AGAINST INSURANCE LEGAL CERTAINTY IN INDONESIA - Theo Julian Rorong; Benny Djaja (Jurnal Scientia, 2023)
They apply the Principle of Legal Certainty in Supreme Court Decision Number 647 K/Pdt.Sus-Bankruptcy/2021 is not applied properly, when the status of PT Asuransi Jiwa Kresna life is declared bankrupt, the most disadvantaged are the customers, the judge should reject the application of PKPU Kresna Life, because the applicant is not a party who has legal standing make a PKPU Application or Bankruptcy Statement, Judge's Consideration in Supreme Court Decision Number 647 K/Pdt.Sus-Bankruptcy/2021 granted the cassation application filed by the Cassation Applicants and canceled the Commercial Court Decision at the Central Jakarta District Court Number 389/Pdt.Sus-PKPU/2020/PN Niaga Jkt. Pst juncto Temporary PKPU Number 389/Pdt.Sus- PKPU/2020/PN Niaga Jkt. PSt poses problems in the implementation of the insurance business considering that insurance or protection is an activity that aims to avoid and delegate risks from one party to another. The judge rejected Kresna Life's PKPU application, because the applicant was not the competent party to apply for PKPU, but granted the PKPU application. The Financial Services Authority should have recommended the Insurance PKPU application, but in this case the Commercial Court Judge granted the PKPU application which should not be accepted, by granting the PKPU application has subsequent legal implications. In the request of Cassation, the Supreme Court Justice accepted the petitioner's application so that PT Asuransi Jiwa Kresna was declared bankrupt. Because the contradiction between the Supreme Court decision and the Insurance Law creates legal uncertainty for insurance customers. In the judge's consideration, the judge needs to be more careful in deciding cases so that the judge does not comply with professional obligations. As the judge needs to be more careful, it has long consequences for the next legal process.